2019
DOI: 10.1103/physrevaccelbeams.22.054502
|View full text |Cite
|
Sign up to set email alerts
|

Nondipolarity of axial channeling radiation at GeV beam energies

Abstract: We consider the nondipolarity of axial channeling radiation generated in a tungsten single crystal at electron-beam energies of several GeV. The calculations are based on the realistic axial continuous potential. It could be shown that, compared to the dipole approximation, the nondipole approximation results in a considerable variation of the channeling radiation spectrum. In a simulation of positron production via conversion of γ radiation into e þ e − pairs, the observed effect may play an important role.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 32 publications
1
8
0
Order By: Relevance
“…The direct simulation of ChR in Geant4 would be very useful, e.g., for simulation of hybrid positron sources which might possibly be used in future electron-positron collider facilities. It has been demonstrated that the created module provides predictable results which coincide with those obtained by our former Mathematica ChR simulation codes [28,29,31,32] and available experimental data [13,47,56]. The newly created module simulates planar ChR applying the classical approach in dipole approximation.…”
Section: Jinst 16 P12042 4 Conclusionsupporting
confidence: 61%
See 4 more Smart Citations
“…The direct simulation of ChR in Geant4 would be very useful, e.g., for simulation of hybrid positron sources which might possibly be used in future electron-positron collider facilities. It has been demonstrated that the created module provides predictable results which coincide with those obtained by our former Mathematica ChR simulation codes [28,29,31,32] and available experimental data [13,47,56]. The newly created module simulates planar ChR applying the classical approach in dipole approximation.…”
Section: Jinst 16 P12042 4 Conclusionsupporting
confidence: 61%
“…Here we restrict to dipole ChR generated during planar channeling of electrons or positrons. A more detailed description of ChR, including dipole as well as nondipole approximations for both planar and axial channeling, is given in our previous works [27][28][29][30][31][32].…”
Section: Brief Theoretical Descriptionmentioning
confidence: 99%
See 3 more Smart Citations